The Construction of Orientalism in Doris Lessing's The Grass is Singing - Bilqis, Bahiroh; Setiawan, Ikwan; Supiastutik, Supiastutik (Faculty of Letters, Universitas Abdurachman Saleh Situbondo, 2023)
This article studies the construction of Orientalism in the novel The Grass is Singing by Doris Lessing. Doris Lessing is a British writer born in Persia who won the Nobel Prize for Literature in 2007. As a white writer, Lessing is known as a writer who fights for the rights of the black community. Still, in this novel, she sharpens the negative image of the blacks as described in the theory of Orientalism. Orientalism focuses on the West’s view of the East. In the novel, Orientalism was carried out by The West against The East, represented by Mary Turner as white people and Moses as the black. This study aims to dismantle the Orientalist discourse in the novel. The study applied the theory of Orientalism proposed by Edward Said (1979). The Orientalist discourse in The Grass is Singing is constructed in the form of stereotypes and oppression against the black people in Southern Rhodesia. Racism, colonialism, and the politics of Apartheid done by white people in the novel showcase the white superiority toward the inferior black.